2021
DOI: 10.2337/db20-0845
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Antigen Arrays Efficiently Deliver Peptides and Arrest Spontaneous Autoimmune Diabetes

Abstract: Antigen-specific immunotherapy (ASIT) offers a targeted treatment of autoimmune diseases that selectively inhibits autoreactive lymphocytes, but there remains an unmet need for approaches that address the limited clinical efficacy of ASIT. Soluble antigen arrays (SAgAs) deliver antigenic peptides or proteins in multivalent form, attached to a hyaluronic acid backbone using either hydrolysable linkers (hSAgAs) or stable click chemistry linkers (cSAgAs). They were evaluated for the ability to block spontaneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Thus, reestablishing tolerance is a lengthy process in which the phenotype of specific T cells is gradually altered over repeated exposures to autoantigens. The response to pDNA-encoded p79 was similar, albeit less pronounced, to the response to p79-carrying soluble antigen arrays ( 5 ). Induction of p79-reactive CD4+ T cells with anergic (CD73+ FR4+) and suppressive (IL-10+) phenotype was seen with both approaches.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Thus, reestablishing tolerance is a lengthy process in which the phenotype of specific T cells is gradually altered over repeated exposures to autoantigens. The response to pDNA-encoded p79 was similar, albeit less pronounced, to the response to p79-carrying soluble antigen arrays ( 5 ). Induction of p79-reactive CD4+ T cells with anergic (CD73+ FR4+) and suppressive (IL-10+) phenotype was seen with both approaches.…”
Section: Discussionmentioning
confidence: 87%
“…Treatment with a single InsB 9–23 (R22E) mimotope in soluble form also significantly prevented the onset of disease in NOD mice, whether it was started at 4 to 6 or 12 to 14 wk of age ( 35 ). More recently, we showed that two peptides in combination (p79 mimotope and hybrid insulin peptide [2.5HIP]) delivered by soluble antigen array starting later, at 8 wk of age, protected 70% of mice ( 5 ). Presentation of a few selected epitopes on MHC molecules displayed on nanoparticles in Pere Santamaria’s successful studies on stage 2 disease also leads to tolerance that spread to other epitopes of the same antigen or others ( 16 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected autoantigens have been administered to patients in the form of proteins or peptides via parenteral, oral or nasal routes, or in the form of protein-encoding DNA plasmids (DNA vaccines) (1, 3). A wide variety of delivery vehicles have been developed and tested to funnel these antigens to specific cell types and/or anatomical locations, including various micro-and nanoparticles (4), and more recently, soluble antigen arrays (5). A DNA-based approach allows the patient's own cells to (i) endogenously express the protein(s) of interest, which may sometimes be challenging to produce recombinantly (e.g.…”
Section: Introductionmentioning
confidence: 99%